Advances in the surgical treatment of breast cancer and postoperative physiotherapy - Opuchlik, Anna; Bocian, Artur; Biskup, Małgorzata; Włoch, Anna; Wróbel, Piotr; Jonak, Robert; Kamińska-Gwóźdź, Ewelina; Ridan, Tomasz (Medical Studies/Studia Medyczne, 2016)
In recent years, radical surgical techniques have been replaced with conserving ones, and a sentinel lymph node biopsy was introduced in the case of routine lymphadenectomy. Subcutaneous amputation with an immediate breast reconstruction or radical breast amputation in Madden modification are used in advanced tumours. Breast conserving surgery and effective neoadjuvant therapy reduce the range of the operation and postoperative complications. Similarly, breast reconstructions do not increase the risk of cancer development, and they do not impede the detection of a local recurrence. This paper presents the most commonly used types of surgery used to treat breast cancer, and the possibility of a surgical reconstruction of the breast. The methods of physiotherapeutic management in particular stages of treating women both after radical surgeries and reconstructions, including the aspect of maintaining their physical activity and mental balance are discussed.